The Application Problem Based Learning (PBL) to Increase Results Study Economicsin Class XI OTKP SMK Negeri 1 Majo - Hulu, Samahati (Berpusi Publishing, 2024)
Objective study This is For study And describe application model Problem Based Learning (PBL) learning as a method to improve results Study chemistry. Study qualitative This use method literature review that is look fortheoretical references that are relevant to the case or problem by tracing the sources source of writing that has been written before. Secondary data analysis techniques use quantitative descriptive approach, in the form of data on student learning outcomes in Economics subjects. Collection technique data is documentation i.e. tracking written sources containing various themes and topics discussed. Data sources come from books, online journal articles, Internet, seminar, results study, And data Which related with material study. StudyThis is done by analyzing the relationship data between the application of the Problem Based model Learning (PBL) with results Study student on eye lesson Economy. Research result shows that the application of the Problem Based Learning (PBL) model can improve results study Economics.